Talent Management in the Digital Era: Utilizing Technology for Recruitment and Retention at PT Arutmin Indonesia - Permana, Yudi; Ambarwati, Riris; Azahraty, Azahraty (International Journal of Economics (IJEC), 2025)
This research examines Talent Management in the Digital Era with a focus on the application of technology for recruitment and retention at PT. Arutmin Indonesia. This company has successfully implemented a technology-based talent management strategy using digital platforms, artificial intelligence and data analysis. Recruitment processes, career development and employee retention management through technology have a positive impact on efficiency, effectiveness and employee satisfaction. The research results show that PT. Arutmin Indonesia faces challenges, including employee resistance to technology and data security. Companies address these challenges through technology training, involvement of IT experts, and implementation of strict data security policies. In facing changes in higher education governance, PT. Arutmin Indonesia also implements innovation and change management strategies. Therefore, the conclusion is to increase technology integration, develop data analysis, and strengthen technology-based skills development. The application of intelligent technologies, such as artificial intelligence, may be a future focus for improving talent management. The conclusion confirms that the technological approach to talent management has had a positive impact and provides valuable insights for other companies that wish to involve technology in managing their human resources in the digital era.